Factors Influencing Medication Adherence Among Hypertensive Patients in A Tertiary Care Hospital, Pune, Maharashtra - Aarti M Nagarkar; Swapnil A Gadhave; Ishor Sharma; Ankita Choure; Donald Morisky (Medsci Publications, 2013)
Background: Chronic illnesses require long term compliance to treatment for positive health outcome. Objectives of this study were (a) to translate and validate eight item Morisky Medical Adherence Scale (MMAS) and (b) to determine association between patient characteristics and medicine adherence in hypertension. Methods: A Cross sectional study among 205 patients, attending medicine OPD in a district hospital, was conducted. Reliability and validity analysis of the translated scale was carried out. Chi square test was used to check associations. Results: Translated scale showed fair reliability (α 0.635) and convergent validity (r=0.859; p<0.01). Medication adherence was significantly associated with age, family type and experience of symptoms. Gender, education, frequency and number of medication did not show any association. Conclusion: The scale can be used as preliminary tool to identify non adherent patients, prior to change of treatment regimen.